2018
DOI: 10.3390/su10124527
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors of Student Relationship Management

Abstract: Due to the upward trend in the globalization of sustainability issues and the intense competitive environment, it is evident that higher education institutions need new strategic approaches to succeed. To this end, the inquiry for this paper has been made into the debate about student relationship management. Going through the literature indicates that institutions have mainly perceived the concept as a technological initiative for solving the problems in individual domains, accompanied by uncoordinated effort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…The increasing scientific communities and institutions are actively involving themselves in augmenting the value for both learners and HEIs to break through social, environmental and economic aspects. They are seizing the opportunity to immerse and implement this phenomenon into tertiary education frameworks in order to expedite the transition to SD [13,14]. Therefore, according to Mandaviya and Dwivedi [15], HEIs (particularly universities) are lagging behind developing this phenomenon into their system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increasing scientific communities and institutions are actively involving themselves in augmenting the value for both learners and HEIs to break through social, environmental and economic aspects. They are seizing the opportunity to immerse and implement this phenomenon into tertiary education frameworks in order to expedite the transition to SD [13,14]. Therefore, according to Mandaviya and Dwivedi [15], HEIs (particularly universities) are lagging behind developing this phenomenon into their system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Network information technology of college student management strategy, through the construction of a college refinement education system, to improve the efficiency of student management [14]. Gholami, H et al believe that with the development of sustainable globalization, college education needs to put forward a new model of student management in order to adapt to today's society and analyze the four key factors for the success of student management in colleges and universities through the quantitative analysis method [15]. Mauro, A. M et al proposed strategies to promote innovation management in higher education by constructing an analytical framework with an understanding of the process of innovation in higher education, combining innovation research and higher education [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gholami, H et al explored the discussion of student relationship management and validated it as a method of measuring analysis. The results showed that knowledge management, student relationship management techniques, student guidance and employee engagement were significant factors affecting knowledge management [15]. Clair, E. B et al, by analyzing the management techniques of classroom students, found that their academic engagement increased after the adoption of appropriate praiseworthiness in the reliability of the teacher, resulting in relatively less behavior in extra-work movement and language [16].…”
Section: Introductionmentioning
confidence: 99%